Inverted impaction of a mesiodens: a case report - (:unkn) unknown (My University, 1999)
Dental, radiological, dermatoglyphic and genetic findings of a patient showing inverted impaction of a mesiodens are presented. It is probable that the inversion of the mesiodens was caused by contact of the incisal edge of the crown of the mesiodens by the apex of the root of the erupting right maxillary central incisor tooth.
Keywords: Humans; Adolescent; Male; Maxilla; Incisor; Pedigree; Dermatoglyphics; Tooth, Supernumerary; Tooth, Impacted